Basic Concept Of Islamic Education Stream And Thought (APPI) - Moh. Ayyub Mustofa; M. Yunus Abu Bakar; Ali Mas’ud (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Islamic education encompasses diverse schools of thought shaped across classical to contemporary eras. Specific Background: The Streams and Paradigms of Islamic Education (APPI) articulate integrative, transformative, and holistic frameworks influenced by figures such as Al-Ghazali, Ibn Sina, Ibn Khaldun, and modern reformists like Muhammad Iqbal. Knowledge Gap: Despite the richness of these paradigms, limited studies synthesize their foundational concepts in relation to contemporary challenges such as digitalization, scientific dichotomy, and the demands of Society 5.0. Aims: This study analyzes the core concepts of APPI as a theoretical basis for developing an adaptive and comprehensive Islamic education system. Results: Findings reveal that APPI is grounded in integrated epistemology—uniting revelation, reason, and experience—supported by the pillars of tarbiyah, ta’lim, and ta’dib. The integrative paradigm bridges religious and modern sciences, the transformative paradigm reorients learning toward student-centered and value-based approaches, and the holistic paradigm fosters multidimensional human development. Novelty: This research offers a unified analytical framework connecting classical thought, modern reformist ideas, and technological demands. Implications: APPI provides a strategic foundation for curriculum reform, character-based pedagogy, and Islamic-aligned digital innovation to strengthen the relevance and authenticity of Islamic education today. Highlights: Highlights the foundational pillars of tarbiyah, ta’lim, and ta’dib in shaping holistic Islamic education. Emphasizes integration of classical thought and modern reform to address contemporary educational challenges. Presents APPI as a strategic framework for curriculum renewal and technology-aligned Islamic pedagogy. Keywords: Islamic Education, APPI, Integrative Paradigm, Transformative Learning, Holistic Framework